Clinical activity of pembrolizumab in metastatic prostate cancer with microsatellite instability high (MSI-H) detected by circulating tumor DNA. Issue 2 (11th August 2020) - Barata, Pedro; Agarwal, Neeraj; Nussenzveig, Roberto; Gerendash, Benjamin; Jaeger, Ellen; Hatton, Whitley; Ledet, Elisa; Lewis, Brian; Layton, Jodi; Babiker, Hani; Bryce, Alan; Garje, Rohan; et al.
Abstract : To report a multi-institutional case series of patients with advanced microsatellite instability high (MSI-H) prostate adenocarcinoma identified with clinical cell-free DNA (cfDNA) next-generation sequencing (NGS) testing and treated with immune checkpoint inhibitors. Retrospective analysis of patients with metastatic castration-resistant prostate cancer (mCRPC) and MSI-H tumor detected by a commercially available cfDNA NGS assay Guardant360 (G360, Guardant Health) at eight different Academic Institutions in the USA, from September 2018 to April 2020. From a total of 14 MSI-H metastatic prostate cancer patients at participating centers, nine patients with mCRPC with 56% bone, 33% nodal, 11% liver and 11% soft-tissue metastases and a median PSA of 29.3 ng/dL, were treated with pembrolizumab after 2 lines of therapy for CRPC. The estimated median time on pembrolizumab was 9.9 (95% CI 1.0 to 18.8) months. Four patients (44%) achieved PSA50 after a median of 4 (3–12) weeks after treatment initiation including three patients with >99% PSA decline. Among the patients evaluable for radiographic response (n=5), the response rate was 60% with one complete response and two partial responses. Best response was observed after a median of 3.3 (1.4–7.6) months. At time of cut-off, four patients were still on pembrolizumab while four patients discontinued therapy due to progressive disease and one due to COVID-19 infection. Half of the patients with PSA50 had both MSI-H and pathogenic alterations in BRCA1 and BRCA2 in their G360 assays. The use of liquid biopsy to identify metastatic prostate cancer patients with MSI-H is feasible in clinical practice and may overcome some of the obstacles associated with prostate cancer tumor tissue testing. The robust activity of pembrolizumab in selected patients supports the generalized testing for MSI-H.